LIVING VALUES EDUCATION DAN SURAT CINTA UNTUK NABI: Pendidikan Menghidupkan Nilai Damai di Indonesia - Bambang Qomaruzzaman; Ahmad Gibson Al Bustomi; Busro Busro (IAIN Ponorogo, 2018)
Abstract: A study by PPIM (2017) which indicates increased intolerance among Indonesian Muslim students encourages the emergence of an Islamic education model that emphasizes the value of peace in a collective life. Islamic religious education (PAI), has been focusing on the mastery of Islamic teachings without being linked to the model of relations and communication with other